The likelihood of sunburn in sunscreen users is disproportionate to the SPF. Issue 3 (7th May 2013) - Pissavini, Marc; Diffey, Brian
Summary Background/Objective Sunburn is a common feature in sunscreen users. The purpose of this paper is to estimate the expected frequency and magnitude of sunburn resulting from typical use of sunscreens labelled SPF15 and SPF30 by people spending long periods outdoors in strong summer sunshine. Methods By combining the probability distribution of the measured sun protection factor (SPF) in vivo with those for the average application thickness and the uniformity of application over the skin surface, a simulation model was developed to estimate the variation in delivered protection over the exposed skin surface from consumer use of sunscreens. Results While either sunscreen, if delivering the nominal SPF over the entire exposed skin, would be sufficient to prevent any erythema, the simulation indicates that the combination of the average quantity applied with the variability in thickness over the skin surface will lead to erythema, especially in SPF15 sunscreen users. Conclusion People who intend spending long periods outside in strong sunshine would be better advised to use SPF30 labelled sunscreens than SPF15 sunscreens, and to apply the product carefully over exposed skin if they wish to minimize their risk of sunburn and, by implication, skin cancer.